Variabel Guru sebagai Prediktor Prestasi Akademik Siswa Sekolah Menengah Pertama di Osun West, Nigeria - Abdur-Rafiu, Jamiu; Aliyu, Yunus; Yusuf, Wahab Ishola (Program Pascasarjana UNU Surakarta, 2024)
This study examined the teachers’ variables as predictors of junior secondary school students’ academic performance in Osun West Senatorial District, Nigeria. The target population comprised Islamic Studies teachers and students in junior secondary schools across the ten (10) local government areas in Osun West Senatorial District. Purposive sampling was adopted in selecting 125 Islamic Studies teachers in all the 132 public junior schools in the district and a simple random sampling technique was adopted in selecting 20 Islamic Studies students from each of the 10 Local Government Areas, therefore, 325 respondents were engaged in the study. The questionnaire was employed to collect relevant information from the respondents. Data were analyzed using Percentage, Mean Range, Standard Deviation, and Regression analysis. The study found that factors like teacher confidence, interest in the subject, qualifications, and experience all significantly predicted student performance. It was concluded from the findings of the study that teachers’ variables positively improved students’ understanding of Islamic Studies and predicted their performance. In line with the findings of the study, it was recommended that teachers should be supported through incentives and professional development. The teachers should have a change of attitude towards the teaching of Islamic Studies so that the achievement of universal basic education will not be hindered, those without required teaching qualifications or non-professionals among the Islamic Studies teachers should strive to pursue professional qualifications. Teachers of the subject should improve their pedagogical skills through seminars, Post Graduate Diploma Courses in Education, and workshops.